"Safe Harbor": Evaluation of a professionalism case discussion intervention for the gross anatomy course. Issue 3 (26th August 2013) - Spampinato, Christine M.; Wittich, Christopher M.; Beckman, Thomas J.; Cha, Stephen S.; Pawlina, Wojciech
<x xml:space="preserve">Abstract</x> Medical professionalism is a multifaceted paradigm and is an essential component of medical education. Gross anatomy is a laboratory to teach professionalism, and promoting critical reflection in medical students is a prerequisite to furthering professionalism. The aim of this study was to determine if professionalism case discussions during a Gross Anatomy course improve students' reflections using a validated reflection instrument (12 items; five‐point Likert scale where 1 = Disagree, 2 = Disagree with reservation, 3 = Neutral, 4 = Agree with reservation, 5 = Agree). Four facilitated reflection sessions were aimed at fostering reflective capacity through reflection on elements of professionalism. Results did not show a significant change between pre‐and postintervention reflection scores (3.45 ± 0.61 vs. 3.48 ± 0.51; P = 0.82). Historical control students were found to have significantly higher reflection scores when compared with postintervention students (3.91 ± 0.53 vs. 3.48 ± 0.51; P < 0.001). However, the historical control students were found to have significantly higher professionalism scores (P = 0.001) as compared with the intervention students. Student satisfaction was high, with 25 of 28 (89.2%) students reporting that the sessions should be included as a component of future anatomy courses. While reflection scores were not significantly increased as a result of the intervention, students expressed appreciation for the opportunity to discuss professionalism issues related to the dissection of cadavers. Additionally, the intervention students had both lower professionalism scores and lower reflection scores, which supports the idea that highly professional students are more capable of reflecting on professionalism. Future studies should determine whether this case discussion intervention improves objective measures of professionalism. Anat Sci Educ 7: 191–198. © 2013 American Association of Anatomists.